ANALISIS FUNGSI POKOK OPERASIONAL KEPALA SEKOLAH DALAM MENJALANKAN ORGANISASI PENDIDIKAN DAN PENGAJARAN - Takdirmin; Abdal; Regina Afriani; Adiba Rana Sausan; Muh. Agung Moureno H (STKIP Subang, 2026)
This study aims to analyze the main operational functions of school principals in managing educational and instructional organizations. The research problem is based on the suboptimal implementation of principals’ operational roles, which affects the effectiveness of school organizations. This study employed a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation studies. The research subjects included principals, teachers, and educational staff. The results indicate that the principal’s main operational functions consist of planning, organizing, implementing, and supervising educational and instructional activities. Principals play a crucial role in coordinating school resources, creating a conducive working environment, and ensuring that the learning process aligns with educational objectives. The findings also reveal that the effectiveness of school organizations is strongly influenced by the principal’s decision-making ability, organizational communication, and efforts to enhance teacher professionalism. Therefore, optimizing the principal’s operational functions is a key factor in improving the quality of educational and instructional organizations